“I am uncertain about its worth…” Academics’ lived experiences post-PhD - Nendauni, L. (South African Journal of Higher Education, 2026)
This study explored the lived experiences of academics post-PhD, examining their perceptions of the degree’s worth in relation to career stability, intellectual growth, and personal wellbeing. While the PhD is widely regarded as the pinnacle of academic achievement, its practical worth remains contested, particularly in an era of precarious employment and shifting career landscapes. Using a phenomenological approach, this study draws on insights from ten early- and mid-career academics across disciplines. Findings reveal a dual reality: while the PhD enhances intellectual development and research expertise, it often fails to secure stable employment, leading to career uncertainty, financial precarity, and psychological strain. Academics reported unmet career expectations and challenges in translating their doctoral training into non-academic roles, accentuating the misalignment between doctoral education and contemporary job markets. To address these issues, the study advocates for PhD programmes to integrate comprehensive career preparation, mental health support, and clearer job market guidance. A conceptual model is proposed to map academics diverse post-PhD lived experiences, offering insights into how academic and professional trajectories intersect. Through highlighting systemic challenges and areas for reform, this study contributes to ongoing discussions on the evolving role and value of the PhD in academia and beyond.